Robust inhibitory glycinergic transmission and the effect of bafilomycin, folimycin and EIPA: lessons from the auditory brainstem - Pizzi, Erika; Hofmann, Lina N.; Singh, Abhyudai; Friauf, Eckhard (Frontiers in Cellular Neuroscience, 2025)
Sustained synaptic transmission requires the continuous replenishment of released synaptic vesicles (SVs). This process is particularly critical in neuronal circuits that operate at high rates and with high temporal precision, such as those in the auditory brainstem. Here, we investigated the effect of SV (re-)filling on inhibitory synapses between the medial nucleus of the trapezoid body (MNTB) and the lateral superior olive (LSO). These synapses transmit information with high speed and fidelity, properties essential for auditory computations such as sound localization. We specifically examined the role of the vacuolar ATPase (V-ATPase), a proton pump that acidifies the SV lumen to enable neurotransmitter loading. Using patch-clamp recordings in acute mouse slices, we assessed synaptic function under control conditions and during continuous V-ATPase inhibition with bafilomycin or folimycin. Contrary to our initial hypothesis, pharmacological inhibition caused only moderate impairment of sustained transmission. Even under high drug concentrations and intense stimulation (e.g., 100 Hz for 4 min), steady-state responses declined only to ~33% of control. Similar reductions were observed in the replenishment rate, the size of the readily releasable pool, and the cumulative eIPSC amplitude. Quantal size decreased gradually, reaching ~70% of control. Recovery from synaptic depression persisted in the presence of V-ATPase blockade, although it was less efficient. Together, these findings indicate that MNTB-LSO synapses are relatively resistant to V-ATPase inhibition, suggesting that SV replenishment does not rely solely on V-ATPase activity. Alternative acidification mechanisms may contribute, and among potential candidates, the Na+/H+ exchanger isoform NHE6 showed strong immunoreactivity in glycinergic MNTB axon terminals contacting LSO somata. This identifies NHE6 as a promising target for future investigation.